Fruit and vegetables : - Thompson, A. Keith (Blackwell, 2003)
The second edition of this very well-received book, which in its first edition was entitled Postharvest Technology of Fruits and Vegetables, has been welcomed by the community of postharvest physiologists and technologists who found the first edition of such great use. The book covers, in comprehensive detail, postharvest physiology as it applies to postharvest quality, technology relating to maturity determination, harvesting, packaging, postharvest treatments, controlled atmosphere storage, ripening and transportation on a very wide international range of fruits and vegetables.